Conjugated naphthalenone diimide compound as well as preparation method and application thereof
By optimizing the structure of organic electrode materials with conjugated naphthylone diimide compounds, the problem of poor performance of existing electrode materials is solved, and high specific capacity, good rate performance and excellent cycle stability are achieved. It is suitable for new types Energy storage system.
Patent Information
- Application Number
- CN202411624279.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-14
AI Technical Summary
The poor conductivity, insufficient redox active sites and unstable electrochemical properties of existing organic electrode materials limit their application in high-efficiency energy storage equipment.
Conjugated naphthalone diimide compounds are used as electrode materials to enhance multi-electron redox activity and improve conductivity and cyclic stability by optimizing molecular structure and electronic configuration.
It significantly improves the electrochemical specific capacity, rate performance and cycle life of the electrode material, and is suitable for zinc ion batteries and aluminum ion batteries, especially under low temperature conditions, and maintains rapid electron transfer and ion diffusion capabilities.
Smart Images

Figure CN119504754A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrochemical energy storage and energy conversion, and particularly relates to conjugated naphthone diimide compounds and a preparation method and application thereof. Background Art
[0002] With the continuous growth of global energy demand and increasingly stringent environmental protection requirements, traditional fossil energy is gradually being replaced by renewable energy, and the efficient storage and utilization of energy has become the focus of current scientific research. Although lithium-ion batteries are widely used due to their high energy density and good cycle performance, their high cost, resource scarcity and potential safety hazards limit their application in large-scale energy storage. In contrast, aqueous zinc / aluminum ion batteries have become a research direction that has attracted much attention due to their rich material sources, low production costs, high safety and environmental friendliness.
[0003] However, there are still bottlenecks in the performance of electrode materials for aqueous zinc / aluminum ion batteries, especially organic electrode materials. Traditional organic electrode materials have poor conductivity, insufficient redox active sites, and unstable electrochemical performance due to their short-range conjugation and low molecular weight in molecular structure, which limits their application in high-efficiency energy storage devices. How to improve their conductivity, redox activity, and cycle stability through the fine design of molecular structure and optimization of conjugated skeleton has become the key to solving the current problem. Summary of the invention
[0004] In order to solve the problem of poor performance of existing organic electrode materials, the present invention provides conjugated naphthone diimide compounds. The electrode material prepared with the compound has excellent electrochemical stability, high specific capacity, good rate performance and excellent cycle life, and is suitable for new energy storage systems such as zinc ion batteries and aluminum ion batteries.
[0005] The invention also provides a preparation method and application of the conjugated naphthone diimide compounds.
[0006] The present invention is achieved through the following technical solutions:
[0007] The present invention provides a conjugated naphthone diimide compound, the structural formula of the compound is shown in any one of Formulas 1 to 3:
[0008]
[0009] After calculation, the theoretical specific capacities of the compounds shown in formula 1-3 are 260 mAh g -1 , 347mAh g -1 , 374mAh g -1 , the theoretical specific capacity is calculated by the following formula:
[0010]
[0011] Since the method for calculating the theoretical specific capacity of a compound is a method known in the art, the present invention will not describe it in detail.
[0012] Based on the same inventive concept, the present invention provides a method for preparing a conjugated naphthone diimide compound, the preparation method comprising:
[0013] Dissolving 1,4,5,8-naphthalenetetracarboxylic dianhydride and an o-phenylenediamine compound in an acidic solvent and performing dehydration condensation to obtain a mixed solution;
[0014] The mixed liquid is subjected to solid-liquid separation, and the obtained solid is washed and vacuum-dried to obtain a crude product;
[0015] The crude product is placed in a nitric acid solution for purification to obtain a conjugated naphthone diimide compound.
[0016] Furthermore, the 1,4,5,8-naphthalenetetracarboxylic dianhydride and the o-phenylenediamine compound are dissolved in an acidic solvent and then dehydrated and condensed to obtain a mixed solution, which specifically includes:
[0017] 1,4,5,8-naphthalenetetracarboxylic dianhydride and o-phenylenediamine compounds are dissolved in an acidic solvent, and then dehydration condensation is carried out at 90° C. to 110° C. The dehydration condensation reaction time is 22 to 26 hours to obtain a mixed solution.
[0018] Further, the o-phenylenediamine compound includes any one of o-phenylenediamine, 2,3-diaminophenazine and 2,3-diaminonaphthalene-1,4-dione;
[0019] The molar ratio of the 1,4,5,8-naphthalenetetracarboxylic dianhydride to the o-phenylenediamine compound is 1:2.
[0020] Furthermore, the acidic solvent is a mixed solution of acetic acid and ethanol in a volume ratio of 1:1;
[0021] The ratio of the molar amount of the 1,4,5,8-naphthalenetetracarboxylic dianhydride to the volume of the acidic solvent is (1-2) mmol:120 mL.
[0022] Further, the mixed solution is subjected to solid-liquid separation, and the obtained solid is washed and vacuum dried to obtain a crude product, which specifically includes:
[0023] The mixed solution is subjected to solid-liquid separation, and the obtained solid is respectively washed several times by centrifugation with hot acetic acid and deionized water, and then vacuum dried at 60±80° C. to obtain a crude product;
[0024] Wherein, the temperature of the hot acetic acid is 70-90°C.
[0025] Furthermore, the crude product is placed in a nitric acid solution for purification to obtain a conjugated naphthone diimide compound, which specifically includes:
[0026] The crude product is placed in a 20-40 wt% nitric acid solution and purified at 120-140° C. for 5-10 hours to obtain a conjugated naphthone diimide compound;
[0027] Wherein, the ratio of the mass of the crude product to the volume of the nitric acid solution is (100-200) mg:200 mL.
[0028] Based on the same inventive concept, the present invention provides the use of conjugated naphthone diimide compounds in the preparation of organic electrodes or aqueous zinc / aluminum ion batteries.
[0029] Based on the same inventive concept, the present invention provides an aqueous zinc / aluminum ion battery, wherein the aqueous zinc / aluminum ion battery comprises the above-mentioned conjugated naphthone diimide compound.
[0030] Based on the same inventive concept, the present invention provides a method for preparing an aqueous zinc / aluminum ion battery positive electrode, the preparation method comprising:
[0031] Dispersing the conductive additive, the adhesive and the conjugated naphthone diimide compound in a solvent to obtain a dispersion;
[0032] The dispersion is coated on a current collector and vacuum dried to obtain an aqueous zinc / aluminum ion battery positive electrode.
[0033] Furthermore, the conductive additive, the adhesive and the conjugated naphthone diimide compound are dispersed in a solvent to obtain a dispersion, which specifically includes:
[0034] Dispersing the conductive additive, the adhesive and the conjugated naphthone diimide compound in NMP, and then grinding them into a slurry to obtain a dispersion;
[0035] wherein the conductive additive comprises at least one of Ketjen black, super P and carbon nanotubes; at least one of Ketjen black, super P and carbon nanotubes;
[0036] The binder includes at least one of polyvinylidene fluoride, polytetrafluoroethylene and SBR rubber.
[0037] Furthermore, the dispersion is coated on a current collector and vacuum dried to obtain an aqueous zinc / aluminum ion battery positive electrode, which specifically includes:
[0038] The dispersion is coated on the surface of the current collector titanium foil, and vacuum dried at 90-100° C. for 10-14 hours to obtain an aqueous zinc / aluminum ion battery positive electrode.
[0039] Based on the same inventive concept, the present invention also provides a method for preparing an aqueous zinc / aluminum ion battery, wherein the aqueous zinc / aluminum ion battery uses a conjugated naphthone diimide electrode as a positive electrode, a metal zinc / aluminum foil as a negative electrode, and a glass fiber separator to separate the positive electrode and the negative electrode, and then adds an electrolyte to assemble into a button battery;
[0040] Wherein, the conjugated naphthone diimide electrode is prepared by the above-mentioned method for preparing the positive electrode of an aqueous zinc / aluminum ion battery;
[0041] The electrolyte uses zinc perchlorate or aluminum perchlorate as electrolyte and deionized water as solvent.
[0042] One or more technical solutions in the embodiments of the present invention have at least the following technical effects or advantages:
[0043] 1. The conjugated naphthone diimide compound of the present invention is a conjugated compound containing C=O and C=N structural units, has multiple redox active sites, effectively enhances the multi-electron transfer ability of the material, significantly improves the redox potential and the electronic conductivity of the material, and is used to prepare the positive electrode of the battery. The compound relies on its abundant C=O and C=N groups to provide redox active sites, realizing Zn 2+ and Al 3+ The reversible storage significantly improves the electrochemical specific capacity of the electrode material and exhibits excellent cycle stability. At the same time, the π-conjugated structure within the compound molecule effectively inhibits the dissolution of the electrode material in the electrolyte, ensuring that it still has rapid electron transfer and ion diffusion capabilities under low temperature conditions, thereby giving the battery excellent low-temperature electrochemical properties.
[0044] 2. The conjugated naphthone diimide compound of the present invention realizes a multi-electron redox process by optimizing the molecular structure and electronic configuration. This unique conjugated molecular arrangement not only improves the conductivity, but also optimizes the storage capacity of zinc ions and aluminum ions. When used to prepare positive electrode materials, it can show excellent energy storage performance in aqueous zinc / aluminum ion batteries, with a theoretical specific capacity of more than 350 mAh g -1 In practical applications, this material has a -1 The current density was 235 mAh g -1 The high reversible capacity of the battery can also provide about 200 mAh g at the same current density in aqueous aluminum ion batteries. -1The reversible capacity shows excellent energy storage capacity. In addition, the positive electrode material also exhibits excellent rate performance and low-temperature cycle performance, can maintain stable electrochemical properties at high rates, and can be used to prepare aqueous zinc / aluminum ion batteries.
[0045] 3. A method for preparing conjugated naphthone diimide compounds of the present invention. The conjugated naphthone diimide compounds prepared by the method have rich C=O and C=N structural units. The synergistic effect of multiple electroactive centers C=O and C=N enhances the electron transfer ability of the material, thereby enabling the battery to achieve higher electrochemical activity and energy density during discharge, especially in an aqueous environment. The extended aromatic conjugated structure further enhances the dissolution stability of the material, effectively inhibits the dissolution of the material in an aqueous electrolyte, thereby significantly improving the structural stability and cycle life of the electrode material. The method has low production cost and good environmental protection characteristics, and can be widely used in the manufacture of high energy density energy storage devices in the future. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0047] Figure 1 This is a scanned photo of the naphthone diimide organic electrode material obtained in Example 2 of the present invention;
[0048] Figure 2 This is a Fourier infrared spectrum of the naphthone diimide organic electrode material obtained in Example 2 of the present invention;
[0049] Figure 3 The naphthone diimide organic electrode material obtained in Example 2 of the present invention is 0.2A g -1 Electrochemical cycle diagram of room temperature aqueous zinc-ion battery at current density;
[0050] Figure 4 The naphthone diimide organic electrode material obtained in Example 2 of the present invention is 0.2A g -1 Constant current charge and discharge curve of room temperature aqueous zinc ion battery under current density;
[0051] Figure 5 This is the electrochemical rate diagram of the room temperature aqueous zinc ion battery of the naphthone diimide organic electrode material obtained in Example 2 of the present invention;
[0052] Figure 6 The naphthone diimide organic electrode material obtained in Example 2 of the present invention is 0.2A g-1 Low temperature (-50°C) aqueous zinc ion battery cycle diagram under current density;
[0053] Figure 7 The naphthone diimide organic electrode material obtained in Example 2 of the present invention has a conductivity of 0.2 mV s -1 Cyclic voltammogram of room temperature aqueous zinc-ion battery at scan rate.
[0054] Figure 8 The naphthone diimide organic electrode material obtained in Example 2 of the present invention is 0.2A g -1 Electrochemical cycle diagram of room temperature aqueous aluminum ion battery at current density;
[0055] Fig. 9 The naphthone diimide organic electrode material obtained in Example 2 of the present invention is 0.2A g -1 Constant current charge and discharge curve of room temperature aqueous aluminum ion battery under current density. DETAILED DESCRIPTION
[0056] The present invention will be described in detail below in conjunction with specific implementations and examples, and the advantages and various effects of the present invention will be more clearly presented. It should be understood by those skilled in the art that these specific implementations and examples are used to illustrate the present invention, rather than to limit the present invention.
[0057] Throughout the specification, unless otherwise specifically stated, the terms used herein should be understood as meanings commonly used in the art. Therefore, unless otherwise defined, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. In the event of a conflict, the present specification takes precedence.
[0058] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0059] The technical principle of the present invention is as follows:
[0060] The preparation method of the conjugated naphthone diimide compound of the present invention comprises:
[0061] S1. Dissolving 1,4,5,8-naphthalenetetracarboxylic dianhydride and o-phenylenediamine compounds in an acidic solvent and performing dehydration condensation to obtain a mixed solution;
[0062] S2. The mixed solution is subjected to solid-liquid separation, and the solid obtained is washed and vacuum dried to obtain a crude product;
[0063] S3. The crude product is placed in a nitric acid solution for purification to obtain a conjugated naphthone diimide compound.
[0064] Step S1 specifically includes:
[0065] 1,4,5,8-naphthalenetetracarboxylic dianhydride and o-phenylenediamine compounds are dissolved in an acidic solvent, and then dehydration condensation is carried out at 90° C. to 110° C. The dehydration condensation reaction time is 22 to 26 hours to obtain a mixed solution.
[0066] Further, the o-phenylenediamine compound includes any one of o-phenylenediamine, 2,3-diaminophenazine and 2,3-diaminonaphthalene-1,4-dione;
[0067] The molar ratio of the 1,4,5,8-naphthalenetetracarboxylic dianhydride to the o-phenylenediamine compound is 1:2.
[0068] In the present invention, the molar ratio of the 1,4,5,8-naphthalenetetracarboxylic dianhydride to the o-phenylenediamine compound is 1:2, which has the advantage that the molar ratio can ensure that all 1,4,5,8-naphthalenetetracarboxylic dianhydride molecules can fully react with the o-phenylenediamine compound, thereby generating the target product to the greatest extent, and this ratio helps to improve the reaction efficiency and reduce the residue of unreacted products.
[0069] Furthermore, the acidic solvent is a mixed solution of acetic acid and ethanol in a volume ratio of 1:1;
[0070] The ratio of the molar amount of the 1,4,5,8-naphthalenetetracarboxylic dianhydride to the volume of the acidic solvent is (1-2) mmol:120 mL.
[0071] In the present invention, the acidic solvent adopts a mixed solution of acetic acid and ethanol in a volume ratio of 1:1, which has the advantage that acetic acid is a highly polar acidic solvent that can effectively dissolve many organic and inorganic compounds, while ethanol has good dissolving power and low polarity. Mixing acetic acid and ethanol in a ratio of 1:1 can form a mixed solvent system with both polar and non-polar properties, further improving the dissolving power and ensuring the full dissolution and uniform dispersion of the reactants. In addition, the mixed solution of acetic acid and ethanol can inhibit the occurrence of some unnecessary side reactions while promoting chemical reactions.
[0072] Step S2 specifically includes:
[0073] The mixed solution is subjected to solid-liquid separation, and the obtained solid is respectively washed several times by centrifugation with hot acetic acid and deionized water, and then vacuum dried at 60±80° C. to obtain a crude product;
[0074] Wherein, the temperature of the hot acetic acid is 70-90°C.
[0075] In the present invention, the advantage of washing the obtained solid matter several times by centrifugation with acetic acid and deionized water at 70-90°C is that acetic acid can effectively dissolve and remove organic impurities or by-products in the solid matter under high temperature conditions. This process helps to purify the surface of the material and make it purer. The use of high-temperature acetic acid helps to activate the surface of the material and make the surface structure of the material more regular by dissolving unstable surface substances. This has a positive effect on the performance of the material in subsequent reactions or applications. After washing with acetic acid, a small amount of acidic substances may remain on the surface of the material. Using deionized water for multiple washings can effectively neutralize and remove these acidic residues to avoid adverse effects on material performance.
[0076] Step S3 specifically includes:
[0077] The crude product is placed in a 20-40 wt% nitric acid solution, and then subjected to an oxidation reaction at 120-140° C. for 5-10 hours to obtain a conjugated naphthone diimide compound;
[0078] Wherein, the ratio of the mass of the crude product to the volume of the nitric acid solution is (100-200) mg:200 mL.
[0079] In the present invention, the advantage of placing the crude product in a 20-40wt% nitric acid solution is that the nitric acid solution can oxidize and remove certain unwanted small organic molecule impurities, thereby improving the purity of the product. This purification effect helps to improve the performance and quality of the final material. The advantage of performing the purification reaction at 120-140°C is that at this temperature, the solubility and reactivity will increase, making it easier to separate impurities from the target product, thereby improving the purification effect, which helps to more effectively remove impurities that are difficult to remove in the solution.
[0080] The conjugated naphthone diimide compounds of the present application, their preparation methods and applications are described in detail below in combination with examples and experimental data.
[0081] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.
[0082] In the following embodiments, the battery performance test adopts the Xinwei battery test system and the Princeton electrochemical workstation. The low temperature test requires that the battery is placed in a low temperature test box at -50°C for testing.
[0083] Example 1
[0084] This embodiment provides a method for preparing a conjugated naphthone diimide compound, which specifically includes:
[0085] Step 1: 1,4,5,8-naphthalenetetracarboxylic dianhydride (1 mmol) and 2,3-diaminonaphthalene-1,4-dione (2 mmol) are used as raw materials, dissolved in an acidic solvent (120 mL) and subjected to a high-temperature dehydration condensation reaction to obtain a crude product; the acidic solvent is a mixed solution of acetic acid and ethanol in a volume ratio of 1:1, nitrogen (N2) is introduced as an inert gas protection, the reaction temperature is 100°C, and the reaction time is 24 hours;
[0086] Step 2: After the obtained mixed solution is filtered, the solid product is centrifuged and washed 5 times with hot acetic acid (80°C) and deionized water respectively, and the obtained solid product is vacuum dried at 60°C.
[0087] Step 3: The crude product (150 mg) obtained in step 2 was refluxed with 30 wt % nitric acid (200 mL) at 140° C. for 3 h, then centrifuged and washed 5 times with deionized water, and vacuum dried at 60° C. to obtain an organic compound represented by formula 3.
[0088] In addition, the synthesis method of the compound of formula (1) is as follows:
[0089] Step 1: 1,4,5,8-naphthalenetetracarboxylic dianhydride (1 mmol) and o-phenylenediamine (2 mmol) are used as raw materials, dissolved in an acidic solvent and subjected to a high-temperature dehydration condensation reaction to obtain a crude product; the acidic solvent is a mixed solution of acetic acid and ethanol in a volume ratio of 1:1 (120 mL), nitrogen (N2) is introduced as an inert gas protection, the reaction temperature is 100°C, and the reaction time is 24 hours;
[0090] Step 2: After the obtained mixed solution is filtered, the solid product is centrifuged and washed 5 times with hot acetic acid (80°C) and deionized water respectively, and the obtained solid product is vacuum dried at 60°C.
[0091] Step 3: The crude product obtained in step 2 (150 mg) was treated with 30 wt% nitric acid (200 mL) at 140°C for 3 h, then centrifuged and washed 5 times with deionized water, and vacuum dried at 60°C to obtain an organic compound represented by formula (1).
[0092] The synthesis method of the compound of formula (2) is as follows:
[0093] Step 1: 1,4,5,8-naphthalenetetracarboxylic dianhydride (1 mmol) and 2,3-diaminophenazine (2 mmol) are used as raw materials, dissolved in an acidic solvent, and subjected to a high-temperature dehydration condensation reaction to obtain a crude product; the acidic solvent is a mixed solution of acetic acid and ethanol in a volume ratio of 1:1 (120 mL), nitrogen (N2) is introduced as an inert gas protection, the reaction temperature is 100°C, and the reaction time is 24 hours;
[0094] Step 2: After the obtained mixed solution is filtered, the solid product is centrifuged and washed 5 times with hot acetic acid (80°C) and deionized water respectively, and the obtained solid product is vacuum dried at 60°C.
[0095] Step 3: The crude product obtained in step 2 (150 mg) was treated with 30 wt% nitric acid (200 mL) at 140°C for 3 h, then centrifuged and washed 5 times with deionized water, and vacuum dried at 60°C to obtain an organic compound represented by formula (2).
[0096] Example 2
[0097] The compound obtained in the above example, Ketjen black and polyvinylidene fluoride (PVDF) were mixed with N-methylpyrrolidone (NMP) solution in a mass ratio of 60:30:10, ground into a well-dispersed slurry in an agate mortar, and then evenly coated on a titanium foil current collector, vacuum dried at 80°C for 12 hours to prepare a working electrode (i.e., naphthone diimide organic electrode material). The working electrode pole piece was used as the positive electrode, the metal zinc foil was used as the negative electrode, the glass fiber membrane was used as the diaphragm, and 3M zinc perchlorate (Zn(ClO4)2) was used to assemble a 2032 button cell. The test voltage range was 0.4V-1.6V vs Zn / Zn 2+ .
[0098] In addition, the aluminum ion battery positive electrode preparation method is as follows:
[0099] The compound obtained in the above example, Ketjen black and polyvinylidene fluoride (PVDF) were mixed with N-methylpyrrolidone (NMP) solution in a mass ratio of 60:30:10, ground into a well-dispersed slurry in an agate mortar, and then evenly coated on a titanium foil current collector, vacuum dried at 80°C for 12 hours to prepare a working electrode (i.e., naphthone diimide organic electrode material). The working electrode pole piece was used as the positive electrode, the metal zinc foil was used as the negative electrode, the glass fiber membrane was used as the diaphragm, and 1MAl(ClO4)3 solution was used as the electrolyte (configuration) to assemble a 2032 button cell. The test voltage range was 0.2-1.05vs Al / Al 3+ .
[0100] Figure 1 This is a scanned photo of the naphthone diimide organic electrode material (Formula 3) obtained in this example. The material exhibits a distinct rod-like structure morphology, demonstrating its microscopic morphological characteristics during the preparation process.
[0101] Figure 2The Fourier infrared spectrum of the naphthone diimide organic electrode material (Formula 3) obtained in this embodiment. The Fourier infrared spectrum shows that the NH stretching vibration peak in 2,3-diaminonaphthalene-1,4-dione is also significantly weakened or disappears, indicating that the amino group participates in the reaction and forms a new bond. The CN vibration peak appears in the spectrum of the final product, indicating the formation of the imide structure. The changes in the above peaks indicate that the raw material has been successfully converted into the target product naphthone diimide organic electrode material.
[0102] Figure 3 The three compounds shown in formula 1-3 were shown to have a -1 Electrochemical cycling performance of room temperature aqueous zinc ion batteries at current density. It can be seen that with the increase in the number of cycles, the capacity retention rate of the electrode material of compound 3 (Formula 3) during charge and discharge is high, and the coulombic efficiency is close to 100%. This shows that the material has good cycle stability and high coulombic efficiency during long cycles, while compound 1 (Formula 1) and compound 2 (Formula 2) show different degrees of capacity decay, especially compound 1, whose capacity decay is more obvious, indicating that its structure may have undergone irreversible changes during the cycle.
[0103] Figure 4 It can be seen from the constant current charge and discharge curves of the three compounds that the discharge curve of compound 3 has a more obvious platform near about 0.8V. The voltage corresponding to the platform reflects the main electrochemical reaction process of the naphthone diimide organic electrode material in the aqueous zinc ion battery, which is usually related to the embedding and de-embedding behavior of zinc ions. The voltage platforms of compounds 1 and 2 fluctuate greatly, especially the discharge platform of compound 1 is lower, indicating that its energy storage capacity is limited.
[0104] Figure 5 The electrochemical rate performance of the three compounds as positive electrodes for aqueous zinc-ion batteries at room temperature is shown. The data show that the electrode material maintains good specific capacity and stable coulombic efficiency at different rates, especially at high rates, and can still maintain high electrochemical performance, demonstrating its excellent rate performance and cycle stability. However, compounds 1 and 2 show low capacity at high current density, especially at 20A g -1 When , compound 1 almost lost its capacity.
[0105] Figure 6 The three compounds were shown to have a -1 The cycling performance of aqueous zinc-ion batteries at low temperature (-50°C) under current density. The results show that even in extremely low temperature environments, the electrode material still exhibits a high specific capacity and a very stable capacity retention rate. In contrast, the specific capacities of compounds 2 and 1 are lower, maintaining at about 85 mAh g -1and 55mAh g -1 This indicates that compound 3 has better electrochemical stability and energy storage capacity at low temperatures.
[0106] Figure 7 The three compounds were shown to have a 0.2 mV s -1 Cyclic voltammetry curve (CV graph) of room temperature aqueous zinc ion battery at scanning rate. From the graph, two pairs of obvious redox peaks can be clearly seen, indicating that the material has good redox reaction activity in the electrochemical process. These two pairs of peaks correspond to Zn 2+ The insertion and deinsertion processes of the material verify the reversible zinc storage performance of the material. The two pairs of reversible redox reactions can be attributed to the zinc association / dissociation processes on the C=O and C=N groups. In comparison, the redox peaks of compounds 1 and 2 are more dispersed and the peak currents are lower, reflecting the poor reversibility and charge transfer kinetics. Compound 3 has higher electrochemical reaction activity and can more effectively promote the electrode reaction process.
[0107] Figure 8 The three compounds were shown to have a -1 Electrochemical cycling performance of the positive electrode of room temperature aqueous aluminum ion battery at current density. As can be seen in the figure, the specific capacity of the electrode material is about 200mAh g -1 , and maintained good capacity stability during multiple cycles, indicating its excellent electrochemical stability. In contrast, the specific capacity of compound 1 was only maintained at 100 mAh g -1 This result shows that the material has excellent cycle performance in aqueous aluminum ion batteries and can maintain a high specific capacity under long-term cycles.
[0108] Fig. 9 The three compounds were shown to have a -1 The charge-discharge curves under different current densities. Compound 3 exhibits two obvious voltage platforms and a specific capacity close to 200 mAh g -1 , showing excellent voltage stability and high energy density, with the best electrochemical performance. In contrast, the voltage platform of compound 2 and compound 1 is lower, and the specific capacity is also lower than that of compound 3.
[0109] In summary, the naphthone diimide organic electrode material (Compound 3) prepared in the present invention has excellent electrochemical properties when applied to positive electrode materials of aqueous zinc / aluminum ion batteries.
[0110] Compared with the prior art, the advantages of the present invention are:
[0111] 1. Significantly improved electrochemical performance: By introducing multiple electroactive centers (such as C=O, C=N groups), the multi-electron redox process is effectively realized, the redox potential is improved, and the electronic conductivity of the material is enhanced, thereby significantly improving the specific capacity and rate performance of the electrode.
[0112] 2. Excellent cycle stability: The introduction of the extended aromatic conjugated structure significantly reduces the solubility problem of the material in an aqueous environment, enhances its structural stability, ensures the performance stability of the battery during long-term cyclic use, and is suitable for the application of aqueous zinc ion and aluminum ion batteries.
[0113] 3. High reversible capacity: The organic cathode material of the present invention has a high reversible capacity of 0.2A g -1 A current density of 235 mAh g -1 The high reversible capacity of the aqueous aluminum-ion battery is 200 mAh g -1 The reversible capacity shows excellent energy storage capability.
[0114] 4. Broad application prospects: The organic electrode material of the present invention is suitable for aqueous zinc / aluminum ion batteries, especially for aqueous zinc ion and aluminum ion batteries. It has low production cost, environmental protection characteristics and high energy storage efficiency, and can be widely used in future high energy density energy storage devices.
[0115] Finally, it should be noted that the terms "comprises," "includes," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements that are inherent to such process, method, article, or apparatus.
[0116] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.
[0117] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A conjugated naphthone diimide compound, characterized in that: The structural formula of the compound is shown in any one of Formulas 1 to 3:
2. The method for preparing the conjugated naphthone diimide compound according to claim 1, characterized in that: The preparation method comprises: Dissolving 1,4,5,8-naphthalenetetracarboxylic dianhydride and an o-phenylenediamine compound in an acidic solvent and performing dehydration condensation to obtain a mixed solution; The mixed liquid is subjected to solid-liquid separation, and the obtained solid is washed and vacuum-dried to obtain a crude product; The crude product is placed in a nitric acid solution for purification to obtain a conjugated naphthone diimide compound.
3. The method for preparing the conjugated naphthone diimide compound according to claim 2, characterized in that: The method of dissolving 1,4,5,8-naphthalenetetracarboxylic dianhydride and o-phenylenediamine compounds in an acidic solvent and then performing dehydration condensation to obtain a mixed solution specifically comprises: 1,4,5,8-naphthalenetetracarboxylic dianhydride and o-phenylenediamine compounds are dissolved in an acidic solvent, and then dehydration condensation is carried out at 90° C. to 110° C. The dehydration condensation reaction time is 22 to 26 hours to obtain a mixed solution.
4. The method for preparing the conjugated naphthone diimide compound according to claim 3, characterized in that: The o-phenylenediamine compound includes any one of o-phenylenediamine, 2,3-diaminophenazine and 2,3-diaminonaphthalene-1,4-dione; The molar ratio of the 1,4,5,8-naphthalenetetracarboxylic dianhydride to the o-phenylenediamine compound is 1:2; The acidic solvent is a mixed solution of acetic acid and ethanol in a volume ratio of 1:1; The ratio of the molar amount of the 1,4,5,8-naphthalenetetracarboxylic dianhydride to the volume of the acidic solvent is (1-2) mmol:120 mL.
5. The method for preparing the conjugated naphthone diimide compound according to claim 2, characterized in that: The mixed liquid is subjected to solid-liquid separation, and the obtained solid is washed and vacuum dried to obtain a crude product, which specifically includes: The mixed solution is subjected to solid-liquid separation, and the obtained solid is respectively washed several times by centrifugation with hot acetic acid and deionized water, and then vacuum dried at 60±80° C. to obtain a crude product; Wherein, the temperature of the hot acetic acid is 70-90°C; The crude product is placed in a nitric acid solution for purification to obtain a conjugated naphthone diimide compound, which specifically includes: The crude product is placed in a 20-40 wt% nitric acid solution and purified at 120-140° C. for 5-10 hours to obtain a conjugated naphthone diimide compound; Wherein, the ratio of the mass of the crude product to the volume of the nitric acid solution is (100-200) mg:200 mL.
6. Use of the conjugated naphthone diimide compound as claimed in claim 1 in the preparation of organic electrodes or aqueous zinc / aluminum ion batteries.
7. An aqueous zinc / aluminum ion battery, characterized in that: The aqueous zinc / aluminum ion battery comprises the conjugated naphthone diimide compound according to claim 1.
8. A method for preparing an aqueous zinc / aluminum ion battery positive electrode, characterized in that: The preparation method comprises: Dispersing a conductive additive, a binder and the conjugated naphthone diimide compound according to claim 1 in a solvent to obtain a dispersion; The dispersion is coated on a current collector and vacuum dried to obtain an aqueous zinc / aluminum ion battery positive electrode.
9. The method for preparing a positive electrode for an aqueous zinc / aluminum ion battery according to claim 8, characterized in that: The conductive additive, the adhesive and the conjugated naphthone diimide compound according to claim 1 are dispersed together in a solvent to obtain a dispersion, specifically comprising: Dispersing the conductive additive, the adhesive and the conjugated naphthone diimide compound according to claim 1 in N-methylpyrrolidone, and then grinding them into a slurry to obtain a dispersion; Wherein, the conductive additive comprises at least one of Ketjen black, super P and carbon nanotubes; The adhesive comprises at least one of polyvinylidene fluoride, polytetrafluoroethylene and SBR rubber; The dispersion is coated on a current collector and vacuum dried to obtain an aqueous zinc / aluminum ion battery positive electrode, which specifically includes: The dispersion is coated on the surface of the current collector titanium foil, and vacuum dried at 90-100° C. for 10-14 hours to obtain an aqueous zinc / aluminum ion battery positive electrode.
10. A method for preparing an aqueous zinc / aluminum ion battery, characterized in that: The aqueous zinc / aluminum ion battery uses a conjugated naphthone diimide electrode as a positive electrode, a metal zinc / aluminum foil as a negative electrode, a glass fiber separator to separate the positive electrode and the negative electrode, and then adds an electrolyte to assemble into a button battery; Wherein, the conjugated naphthone diimide electrode is prepared by the method for preparing a positive electrode of an aqueous zinc / aluminum ion battery according to claim 8 or 9; The electrolyte uses zinc perchlorate or aluminum perchlorate as electrolyte and deionized water as solvent.
Citation Information
Patent Citations
Preparation method and application of nitrogen-doped porous carbon negative electrode material
CN107919461A
High-capacity metal ion battery organic electrode material, and preparation method and application thereof
CN112961163A
Naphthalimide derivative, preparation method thereof and application of naphthalimide derivative in flow battery
CN116178370A
Electric device and photoelectric conversion device comprising the same
US5006915A